KONTRIBUSI PONDOK PESANTREN DARUSSALAM SUNGAI MANCUR TERHADAP PEMBINAAN BIDANG SOSIAL KEAGAMAAN DI KABUPATEN BUNGO - Ahmad Basri (Jurnal Interprof, 2017)
Formula of is problem of research identified to two problems, that is how is religious construction form Maisonette Boarding School of Darussalam Sungai Mancur to our society; and how do role Maisonette Boarding School of Modern Darussalam Sungai Mancur in giving construction of religion in Sub-Province Bungo This research aim to to know construction of done religion Maisonette Boarding School of Darussalam Sungai Mancur for moslem society in SubProvince Bungo; to explain the activity forms construction of the religion is to be done Maisonette Boarding School of of Darussalam Sungai Mancur; and to discriptive construction of done religion Maisonette Boarding School of of Darussalam Sungai Mancur in improving the social aspect of moslem economics in Sub-Province Bungo. Research result expected can be of benefit to government Sub-Province Bungo upon which consideration in taking policy at sector construction of religion in supporting the development process; for Maisonette Boarding School of Darussalam Sungai Mancur specially, and maisonette institute boarding school in Sub-Province Bungo in general, can be made upon which reference in improving the religious construction activity and education quality for society in him region; for wide society upon which input in improving human resource quality and prosperity; and to all researchers is upon which reference and materials compare to do research of continuation. Data collected by executing the observation, interview, with leader boarding school, teachers, santri and elite figure, and also study various needed document. Data in analysis by using technique analyse the data qualitative model interaktif told by Miless and Huberman (1992) consisting of the data collecting, data discount, presentation of data conclude. Data checked by doing extention of participation, the perception more careful and coleage discussion. Research result indicate that construction of done religion Maisonette Boarding School of Darussalam Sungai Mancur done with two model, that is model activity of mission and religious service model to society. Role Maisonette Boarding School of Darussalam Sungai Mancur in giving construction of religion instructed to sharpen ability teachers and santri and improve the coordination with society, local government Sub- Province BUngo and Department of Religious Representative Office of Bungo.